New earthworms of the Pheretima urceolata species group (Oligochaeta: Megascolecidae) from southern Luzon, Philippines - Hong, Yong; James, Samuel W. (Zootaxa, 2009)
Earthworm specimens were collected from the Bicol region, southern Luzon Island, the Philippines. Seven species of the genus Pheretima Kinberg, 1867 are described from Bicol: Pheretima bicolensis sp. nov., Pheretima viracensis sp. nov., Pheretima camarinensis sp. nov., Pheretima doriae sp. nov., Pheretima batoensis sp. nov., Pheretima buhiensis sp. nov., and Pheretima gorasi sp. nov. The seven new Pheretima species all key to the urceolata group in Sims & Easton (1972) with a single pair of spermathecal pores in 5/6. Pheretima bicolensis sp. nov. has spermathecal pores 0.05–0.06 circumference apart, copulatory bursae openings 0.14 circumference apart. Pheretima viracensis sp. nov., has spermathecal pores 0.32–0.36 circumference apart; copulatory bursae openings 0.20 circumference apart. Pheretima camarinensis sp. nov., has spermathecal pores 0.18–0.20 circumference apart; copulatory bursae openings 0.19–0.20 circumference apart. Pheretima doriae sp. nov., has spermathecal pores 0.32 circumference apart; copulatory bursae openings 0.32 circumference apart. Pheretima batoensis sp. nov., has spermathecal pores 0.21–0.23 circumference apart; copulatory bursae openings 0.15–0.18 circumference apart. Pheretima buhiensis sp. nov., has spermathecal pores 0.04–0.06 circumference apart; copulatory bursae openings 0.07–0.12 circumference apart. Pheretima gorasi sp. nov., has spermathecal pores 0.06–0.07 circumference apart; copulatory bursae openings 0.10 circumference apart. Descriptions of the new species are provided, including illustrations of the ventral view, and spermathecae.